Inhibition of pancreatic lipase by gallic acid and quercetin equivalent in ultrasonicated Malaysian grown Aquilaria spp. leaves of different particle size / Miradatul Najwa Muhd Rodhi ... [et al.] - Muhd Rodhi, Miradatul Najwa; Ku Hamid, Ku Halim; Hamzah, Fazlena; Kamarul Bahari, Nur Syafiqah; Abdul Rahman, Nur Amira (Universiti Teknologi MARA Shah Alam, 2020)
Pancreatic lipase inhibitory compounds (gallic acid and quercetin) and their inhibition properties were determined in the crude extract of matured leaves from widely grown Aquilaria spp. in Malaysia, which are Aquilaria malaccensis and Aquilaria subintegra. The leaves were dried at 60 °C for 24 hours and undergone a pre-treatment method by using ultrasonication, within 30 minutes of reaction. Dried matured leaves were ground and sieved into particle sizes of 250, 300, 400, 500, and 1000 µm. Each particle size was soaked in distilled water with a ratio of 1% (w/v) for 24 hours, prior to ultrasonication process. Particle size of 250 µm resulted in the highest concentration of gallic acid and quercetin equivalent for both species of Aquilaria, wherein 89.99 mg/ml of gallic acid equivalent and 0.0295 mg/ml of quercetin equivalent were obtained in A. malaccensis crude leaves extract and in A. subintegra crude extract, 101.27 mg/ml and 0.0373 mg/ml were obtained, respectively. Thus, this sample was used in the inhibition study of pancreatic lipase. The concentrations of substrate and enzyme activity prepared were varied in the inhibition kinetics study. Based on the inhibition of pancreatic lipase, the crude leaves extract of both Aquilaria species exhibited the mixed-inhibition which is also known to be the non-competitive inhibition because the reaction mechanism showing the binding of inhibitor to the free pancreatic lipase and pancreatic lipase-substrate complex. This research is one of the fundamental works for future studies on the natural source to control obesity, which is a new direction of the key research in lipase inhibition.